THE ROLE AND SIGNIFICANCE OF THE TERM CONCEPT IN COGNITIVE LINGUISTICS AND LINGUACULTUROLOGY (Conferencea, 2023)
Concepts as elements of consciousness are completely autonomous from language. People often understand words not at the level of their own knowledge, but at the level of the meanings they convey, that is, at the level of concepts. Thus, the meaning of the word is simply an attempt to give a general idea of the content of the expressed concept, to define its certain boundaries, to present certain features of it with a certain word.